L’unica risposta è la prossima domanda. L’esperienza teatrale e il suo mistero: conversazione fra Denis Diderot e Carmelo Rifici (Itinera, 2020)
This interview with Carmelo Rifici, Drama School Director of the Piccolo Teatro di Milano and award-winning theatrical director, discuss on the relationship between some thesis of theatrical aesthetics of the 18th century philosophe Denis Diderot, enclosed in their most complete way in the work Paradox of the actor, and the contemporary reflection on theatre, but also the practice of acting itself.How much does Diderot's thought still question and stimulate the debate on the experience of theatre in its various themes? Without neglecting the contents of this thought, on which 20th century theatre has been questioned a lot and which also emerge in all their facets and possible developments in the interview, during the interesting conversation with Rifici it appears that the true modernity of diderotian reflection and its still generating force today, lies in its asystematic character, in the search for paradox, for perennial question, as a fundamental element for preserving the theatre and its "mystery". It is necessary asking others and themselves questions rather than defining solutions, to restore the theatrical experience, which is the experience of an event, in all its complexity, in diderotian theatrical theory as well as in modern acting practice.
Keywords: Denis Diderot, Carmelo Rifici, theatre, acting, aesthetics of theatre